Investigation on weld quality using different filler metals - Zetty Akhtar, Abd Malek (2012)
Dissimilar welding process yields unwanted disadvantages on the weld joint due to the large difference between stainless steel-aluminium sheets melting points and nearly zeros solid solubility between these two metals. Aluminium AA6061 and stainless steel SUS304 were lap-welded by using Metal Inert Gas (MIG) welding with aluminium filler ER5356 and stainless steel filler ER308LSi. The effect of welding voltage and type of filler metals used to the weld joints were studied. The welding voltage had significance effect to the welding process, as high voltage resulted in poor appearance of the weld joint. Joints between aluminium and stainless steel using aluminium filler have good microstructure as it shows enrichment of eutectic silicon particle, thus increase the hardness of the joint. The intermetallic compound layer occur between heat affected zone and fusion zone. The hardness value of welded seam in this joint range from 60 to 100 HV. The fracture in tensile test occurred at the edge of the joint before derive into welded seam with the highest tensile strength of 104.4 MPa. Meanwhile, aluminium-stainless steel joints using stainless steel filler contains carbide precipitate in its microstructure, which is undesirable in welding process. The enrichment of chromium particles indicates that there is element addition in weld joint throughout welding process. The hardness value of the welded seam range from 180 to 230 HV and the highest tensile strength is 61.76 MPa. Based on this study, it can be concluded that aluminium filler ER5356 is the optimum filler in joining dissimilar metal aluminium AA6061 and stainless steel SUS 304.